(untitled) (Fiep Bulletin - online, 2017)
The objective of this study was to analyze the dermatoglyphic profile of table tennis players through the collection offingerprints. The sample consisted of 24 athletes, 16 males with mean age of 27 ± 5.4 years; And 8 (eight) females with 23.2 ± 5.1years, all of them national level in the Absolute A category. Descriptive statistics were used with measures of central tendency(mean) and dispersion (standard deviation). The Shapiro Wilk test demonstrated normality among the investigated variables,thus opting for parametric tests. The comparative of the samples was given by Student’s t-test for independent samples, adoptingsignificance level p0,05. The Pearson coefficient matrix was used for correlation of the investigated variables and the coefficientof determination, adopting Anova One Way significance level p0,05. Class II became more frequent in table tennis players (52%)for both genders. Analyzed from the first to the fifth of the national ranking there was higher frequency in class II for males, fiveathletes and four for females. In male athletes, it was shown that the higher the LQTS (r = 0.78), the worse the ranking (A = Arcs)showed better placement (r = -0.66). For the findings of the female athletes, the higher the number of D10 the worse theirplacement (r = 0.78) and the higher the presence of L (loops) the better their placement (r = -0.78), the W increases (Werticilos)worsens its placement (r = 0.78). It can be concluded that the investigated athletes possess potentiated strength and potentiablecoordination, being in class II of somato-functional valences. It is noteworthy that these athletes do not occupy the bestinternational placements, either world-wide or Olympic.